Faktor-faktor yang Mempengaruhi Prolaps Organ Panggul di RSUD DR. H. Abdul Moeloek Provinsi Lampung Periode 1 Januari 2014 – 31 Desember 2018 - Fiana Deswita; Ratna Dewi Puspita Sari; Ety Apriliana; Nurul Islamy (MAJORITY, 2021)
Pelvic organ prolapse (POP) is a condition that affects a woman's quality of life. Pelvic organ prolapse can include uterine prolapse, cystocele and rectocele. POP occurs due to weakness of the muscles, ligaments and fascia that support the pelvic organs. This condition can be influenced by factors such as age, parity, menopause, body mass index and occupation. This study aims to determine the relationship of these factors to the incidence of POP. The study is an observational analytic with cross sectional approach, using secondary data from the medical records of gynecological patients at H. Abdul Moeloek Hospital in the period 1 January 2014 to 31 December 2018 with a total sampling technique. Then univariate and bivariate analyzes were performed using the chi-square test. The incidence of POP in the period of 1 January 2014 to 31 December 2018 in the H. Abdul Moeloek Hospital was 33 cases. Factors that had a relationship with the highest risk sequence are parity (p = 0.000; OR 7,959), age (p = 0.002; OR 7,250), menopause (p = 0.014; OR 5.019), body mass index (p = 0.036; OR 3.297) and type of work (p = 0.036; OR 3.297).All factors studied is parity, age, menopause, body mass index and type of work were associated with the incidence of pelvic organ prolapse in patients at H. Abdul Moeloek Hospital, Lampung Province January 2014 to 31 December 2018